Analisis Perbedaan Kepuasan Pembaca Tabloid Gratis Surabaya Shopping Media dan Iklan Pos di Surabaya - Marta, Rustono Farady (Nirmana, 2013)
The underlying motive for someone to read is an attempt to obtain gratification through the media. According to Denis McQuail, there are four typology motives that are used, namely: motive of information (surveillance), motive of personal identity, patterns of integration and social interaction (personal relationship), and entertainment motive (diversion). This study is based on the uses and gratifications theory by analyzing the motives through pre-test questionnaire as an instrument of gratification sought, then post-test questionnaire to determine the real satisfaction (gratification obtained) towards 100 respondents who are included. Quantitative method is used to prove the hypothesis of the study, in which the McNemar test on nominal data for the same population assesses two different objects show the existence of the gap (discrepancy) between the motives with the satisfaction of the reader. This research does not stop until the analysis of the gap between motives and reader satisfaction, but further study to see comparative advertising in the free tabloids "Surabaya Shopping Media" and "Iklan Pos". Two free tabloids can be juxtaposed in a comparison study, due to the same general specifications owned by both. On the other hand, the difference of these two free tabloids are: representing two different company backgrounds in their establishments (company profile), the ideology of the company, product display, advertiser segmentation, tagline and iconic products. The accumulated data at a sub variable level shows that motive variables and satisfaction with free tabloid â€œSurabaya Shopping Mediaâ€ and â€œIklan Posâ€ in this study are defined as an interval scale data, then tested using two sample paired difference test for interval scale data using the short method for t test.